Improvement of Spice Drink Packaging to Improve Product Quality and Competitiveness in UKM Daniyah Sukoharjo - Sri Lestari, Mathilda; Puspita, Maria; Khomariah, Ainur (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2023)
In the era of the Covid 19 pandemic, many people are consuming drinks made from spices to increase their body's immunity. The drinks consumed include ingredients made from ginger, kencur, turmeric and temulawak, just like those produced by UKM Daniyah. The production process at UKM Daniyah is still traditional. The packaging process is also done manually, namely by inserting it into a plastic clip. The packaging also contains a label containing product information. However, the labeling process only uses photocopies, so the packaging process takes a long time. Financial management at UKM Daniyah is also not well documented. So far, financial management has only been recorded in a notebook and manual calculations. These problems have encouraged us, the Bantara Sukoharjo Univet Community Service team to facilitate spice grater equipment and product packaging equipment, assist partners in the packaging process until they are able to carry out packaging properly, and assist partners in financial management until partners can carry out computerized financial management